PROBLEM SOLVING MENUMBUHKAN MINAT BERWIRAUSAHA PADA MAHASISWA MELALUI PENGGUNAAN E-COMMERCE: PROBLEM SOLVING MENUMBUHKAN MINAT BERWIRAUSAHA PADA MAHASISWA MELALUI PENGGUNAAN E-COMMERCE - Nurul Fadilah; M. Chaerul Rizky (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
A marketplace can be a digital platform or place that provides services that make it easier for students to transact between traders and buyers in an online market. Utilizing the Marketplace provides convenience in the business world, considering that problems are increasingly complex, there are more and more competitors and the demand to always follow developments in the global world which requires us to always act creatively and innovatively. It can be seen that Marketplace users as a medium for entrepreneurship come from various groups ranging from large-scale businesses to micro, small and medium businesses. The use of the market space itself is to save marketing and promotion costs, as well as energy and time